Perancangan dan Implementasi Redesign Website di PT. Harmoni Properti Batam : indonesia - WAN, Jed Wan; Sama, Hendi; Firmansyah, Muhamad Dody (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
The internal website of PT. Harmoni Properti Batam previously exhibited several deficiencies in its user interface (UI), which negatively affected the efficiency and comfort of the staff's daily operations. This project aimed to redesign the interface to create a more user-friendly system that enhances workflow effectiveness. The methods employed included observation, interviews, and technical documentation analysis, with the development process conducted by directly editing the source code using PHP Native, CSS, and Bootstrap. The results demonstrated that the new interface significantly improved readability, visual consistency, and navigation ease.